Master Sun on the Art of Gangster Story - Petříček, Miroslav (Iluminace, 2001)
A review of the American action film Ghost Dog - The Way of the Samurai by director Jim Jarmusch.
Keywords: Ghost Dog - The Way of the Samurai 1999; movie review